Copper oxide nanostructures as a potential method for control of zucchini yellow mosaic virus in squash. Issue 8 (10th June 2022) - Derbalah, Aly; Abdelsalam, Ibrahim; Behiry, Said I.; Abdelkhalek, Ahmed; Abdelfatah, Mahmoud; Ismail, Sherin; Elsharkawy, Mohsen Mohamed
Abstract: BACKGROUND: Zucchini yellow mosaic virus (ZYMV) infects cucurbits and has been identified as a major limiting factor in their production. The purpose of this study was to create copper oxide nanostructures (CONS) to control ZYMV in squash plants. Protection of squash against ZYMV was assessed in terms of virus severity, ZYMV concentration, transcription of pathogenesis‐related genes and growth enhancement of treated squash. RESULTS: The findings revealed that squash plants treated with CONS had a significant reduction in disease severity when compared with untreated plants. In squash plants treated with CONS, defense genes associated with the salicylic acid signaling pathway were strongly expressed compared with untreated plants. The structural characteristics of CONS, such as their small size and appropriate shape, added to their excellent anti‐ZYMV efficacy. CONS‐treated squash plants show significantly improved growth traits compared with untreated plants. CONCLUSION: Based on the results of this study, CONS may be a new strategy for the control of ZYMV in squash. This represents an unconventional solution to control this virus, particularly as no chemical pesticides can control viral diseases. © 2022 Society of Chemical Industry. Abstract : This study fabricated copper oxide nanostructures (CONS) to control zucchini yellow mosaic virus (ZYMV) in squash plants. Control was monitored in terms of virus severity, ZYMV concentration and transcription of pathogenesis‐related genes. This is considered the first report of CONS a new ZYMV control approach in squash plants.